PENGEMBANGAN MODEL PENILAIAN PRAKTIK INDUSTRI PADA JOB PERFORMANCE KEAHLIAN PEKERJAAN SOSIAL DAN ILMU KELUARGA - Rohaeni, Neni; Achdiani, Yani; Jubaedah, Yoyoh; Rinekasari, Nenden Rani; Yusuf, Shofa Fithriturrohmi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2022)
This research is motivated by the unavailability of industrial practice assessment instruments on job performance of social work and family science skills by standard demands in social institutions and government agencies. This causes the competence of students when carrying out industrial practices cannot be assessed properly because there is no specific reference in assessing the ability of students. Developing this industrial practice assessment model, it is to clarify and facilitate the process of implementing the practice assessment, so that the implementation of industrial practice can be carried out properly. In addition, there is still a variety of assessment instruments used to assess student job performance in the implementation of Industrial Practice, so that guidance is needed by Standard Operating Procedures in Social Institutions and government agencies. This research aims to develop the Industrial Practice Assessment Model on Job Performance of Social Work and Family Science Expertise. Problem-solving is done using a Research and Development approach, through stages: (1) Preliminary Studies, (2) Model Development, and (3) Model Validation. Industrial Practice Assessment Model on Job Performance competence of social work and family science expertise produced has the advantage of having gone through the stages of needs identification, theoretical analysis, and validation tests through expert judgment practitioners from social institutions and government institutions. The results of validation of industrial practice assessment tools that have been designed are categorized as